PERFORMANCE ANALYSIS OF WATERJET PROPULSION ON UNMANNED SURFACE VEHICLE MODELS - Budiyanto, Muhammad Arif; Ayuningtyas, Hamnah (Journal of Applied Engineering Science, 2021)
Waterjet propulsion on an unmanned surface vehicle is a propulsion system with the working principle of taking water from the bottom of the hull into the turbine to be blown back out and converted into the ship's thrust. The resulting thrust depends on the available water forces. The water spray in the nozzle is generated from the inlet at the bottom of the ship which is assisted by a pump on the waterjet. In the inlet section, this will affect the distribution of flow that will pass through the pump and finally out through the nozzle. The purpose of writing this thesis is to analyze the inlet-passage of the waterjet which is variable with the inlet velocity ratio (IVR) to get the maximum efficiency value of the waterjet propulsion system. The work of this thesis uses the computational fluid dynamics (CFD) method and analytical calculations. The inlet velocity ratio is varied from 0.54, 0.59, 0.67, 0.78, 0.94, 1.18, 1.64, and 2.38 which will be compared the results. From the results of the analysis will be obtained the volume that comes out of the waterjet and the results will be obtained the thrust value. The highest thrust value obtained is based on the variation in the IVR value of 2.38, and the maximum efficiency value is 98%.
Keywords: waterjet, inlet passage, thrust, inlet velocity ratio, efficiency